2018
DOI: 10.1002/jso.25271
|View full text |Cite
|
Sign up to set email alerts
|

The value of a cross‐discipline team‐based approach for resection of renal cell carcinoma with IVC tumor thrombus: A report of a large, contemporary, single‐institution experience

Abstract: Introduction We report the evolution of the largest, contemporary, single‐institution experience with this complex procedure to highlight the value of a cross‐discipline, team‐based approach. Methods Patients from a prospectively maintained database who underwent resection of renal cell carcinoma (RCC) with inferior vena cava (IVC) tumor thrombus from 2005 to 2016 at a single‐institution were included for analysis. Results Of 140 patients, 102 (73%) had tumor thrombus below the level of the hepatic vein conflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
0
17
0
2
Order By: Relevance
“…After excluding 64 patients who did not meet the inclusion criteria, 121 were available for analysis. Table 1 Prior study suggested that surgery for VTT above the hepatic vein is much more di cult than that of VTT below the hepatic vein [12]. Thus, the VTT above the hepatic veins was de ned as high level, while VTT below the hepatic veins was de ned as low level in this study.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…After excluding 64 patients who did not meet the inclusion criteria, 121 were available for analysis. Table 1 Prior study suggested that surgery for VTT above the hepatic vein is much more di cult than that of VTT below the hepatic vein [12]. Thus, the VTT above the hepatic veins was de ned as high level, while VTT below the hepatic veins was de ned as low level in this study.…”
Section: Resultsmentioning
confidence: 82%
“…Even for experienced urologist, perioperative complications cannot be avoided completely. However, popularization of the multidisciplinary collaboration improves the safety of the patients with RCC with VTT, and decreases mortality [12]. In our cohort, a multidisciplinary team, consisting of an urologist, anesthesiologist, cardiac surgeon, general surgeon, critical care physician and radiologist, offered comprehensive and systematic perioperative plan and management for the patients received RNTE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Median OS of the entire cohort was 43.8 months (5-year OS: 43%), and 73.6 months (5-year OS: 59%) for those without metastatic disease. RRT was required in 2 (1%) cases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, when “in situ” renal resection is not possible (multiple, large, or centrally located tumours), authors resorted to performing ECPN with ortho- or heterotopic autotransplantation of the resected kidney [ 12 , 17 ]. Currently, the experience with such operations is not great, but their results are satisfactory [ 12 , 14 , 16 , 17 , 18 , 19 ]. Anyhow, we could not find cases of ECPN with orthotopic replantation under pharmaco-cold ischaemia for RCC complicated by IVC tumour thrombosis in single kidney in the literature.…”
Section: Discussionmentioning
confidence: 99%